1995
DOI: 10.1029/94wr02852
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Anions and Herbicides in a Loamy and a Sandy Field Soil

Abstract: A field experiment was conducted to investigate preferential transport of herbicides and to explore processes that cause rapid movement. Bromide, chloride, and three herbicides (triasulfuron, atrazine, and terbuthylazine) with different mobility characteristics were applied to six 1.4 x 1.4 m field plots on a loamy and a sandy soil. At both sites, three of the plots were covered with a plastic roof 1 month before the beginning of the experiment to achieve different initial water contents between the plots. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 30 publications
(13 reference statements)
2
62
0
1
Order By: Relevance
“…These allow for, locally, up to 100-1000 times faster water fluxes than compared to matrix flow (Beven and Germann, 1982) because capillarity may be neglected in those structures and flow resistances in the direction of the driving potential gradient are much smaller. Flury et al (1994Flury et al ( , 1995 were among the first to develop effective methods to visualize infiltration and flow patterns in heterogeneous field soils by using dye tracer techniques. Today we know of numerous studies that have provided further evidence, demonstrating that that preferential flow in structured soils is indeed the rule rather than the exception (Fig.…”
Section: Infiltration and Vertical Preferential Flowmentioning
confidence: 99%
“…These allow for, locally, up to 100-1000 times faster water fluxes than compared to matrix flow (Beven and Germann, 1982) because capillarity may be neglected in those structures and flow resistances in the direction of the driving potential gradient are much smaller. Flury et al (1994Flury et al ( , 1995 were among the first to develop effective methods to visualize infiltration and flow patterns in heterogeneous field soils by using dye tracer techniques. Today we know of numerous studies that have provided further evidence, demonstrating that that preferential flow in structured soils is indeed the rule rather than the exception (Fig.…”
Section: Infiltration and Vertical Preferential Flowmentioning
confidence: 99%
“…Kamra et al (2001) studied pesticides transport in small soil columns applying non-equilibrium two-region/mobile-immobile model. Flury et al (1995) investigated preferential flow in the field. In this study herbicide was only partly sorbed by the soil matrix.…”
mentioning
confidence: 99%
“…First, the simpler single-continuum model seems inadequate to model the observed VOC concentration data, and second, the last decade of research has shown that, with a few exceptions (e.g., Wierenga, 1991;Hills et al, 1991), preferential flow is pervasive in the vadose zone (Kung, 1990a,b;Ghodrati and Jury, 1990;1992;Li and Ghodrati, 1994;Flury et al, 1994Flury et al, , 1995McCord et al, 1997).…”
Section: Conceptual Models For Subsurface Flow and Transportmentioning
confidence: 99%